The impact of the European crisis in vulnerable households in Europe - Estêvão, P.; Calado, A.; Capucha, L. (Poverty, crisis and resilience, 2020)
Poverty remains a problem in Europe, raising the need for new solutions. In this thought-provoking book the contributors delve deeply into the everyday lives of poor households to see which practices and resources they apply to improve their situations. One of the key findings is that social resilience requires a functioning welfare state operating as a warrantor of common and public goods, on which poor households can build up resilient practices. This insightful book illustrates that in addition to sufficient welfare transfers, there is a need for low-commodified common goods, including public health services, access to housing, education infrastructures and public space. These need to be made available not only for the registered poor but all low-income households. Drawing on over 400 interviews with families and experts across Europe, the chapters demonstrate the need for social policy to become more tolerant towards various forms of small additional income generation and non-commodified values and lifestyles. Poverty, Crisis and Resilience will be a key resource for students and scholars of social policy, poverty research and sociology, while also being of value to social policy practitioners within the charity sector, welfare state administration, social work, politics and counselling.